Impression management: a dramaturgical perspective - Gardner, William L. (Henry Stewart Talks, 2012)
A dramaturgical perspective, The actor (self), Identity, Self-concept, Self-esteem, Values, Motives, Self-monitoring, The stage (setting/context), Audiences, Impression management behavior, Performance (acquisitive impression management), Ingratiation, Self-promotion, Intimidation, Exemplification, Supplication, Association, Nonverbal impression management, Performance (protective impression management): Accounts, apologies, restitution, prosocial behavior, Disclaimers, self-handicapping and disassociation, Reviews (favorability), Reviews (audience response), Acknowledgements and thank you